(untitled) (Studia Prawnicze / The Legal Studies, 1981)
According to binding legislation, boards having jurisdiction over transgressions may pronounce penalties such as: a fine, limitation of liberty and short-term deprivation of liberty (up to three months). Judicial control is exercised only over cases in which a decision of a board concerning principal penalty of short-term deprivation or limitation of liberty was appealed (article 86 of the code of procedure on transgressions). Empirical studies presented here aimed at presenting the practical side of judicial control over decisions of the boards and at the same time, comparing decisions of two different organs pronounced in reference to the same acts. The studies were carried out in two regional courts: for the city of Warsaw and for the district of Praga! They included all attainable files concerning transgressions adjudicated in these courts during 1977 and the first quarter of 1978 (225 cases alltogether). The studies allowed to establish that from the point of view of judicial control the most important is the issue of court proceedings in cases in which the board pronounced unconditional penalty of short-term deprivation of liberty inexpedited proceedings. According to the provisions of the code of procedure on transgressions such penalty is subject to execution immediately after the announcement of the decision and the person punished is put into a penalty institution right after the main trial. Duly instituted appeal from the board’s decision does not hinder or suspend its execution. In no case has the court stayed execution of the penalty inflicted by the board either, although the Supreme Court has made it possible. In many cases partial execution of the penalty resulted in withdrawal of the means of review filed by the accused. A tendency to pronounce a short-term penalty of deprivation of liberty within the limits already executed at the moment of pronouncement of a judgement by a court was also observed in studied cases. In 49 per cent of cases adjudicated as to the merits, court’s estimation of acts of the person punished differed from that of the boards’. In 6 per cent of cases the court totally acquitted the accused and in 42,5 per cent of cases it pronounced a less severe penalty or altogether renounced from inflicting punishment (only once a more severe penalty was pronounced). Basic conclusion drawn from the above-presented studies concerns the need for changes in binding legislation. Such changes should aim at significant widening of the scope of judicial control over decisions of the boards having jurisdiction over transgressions and ameliorating its forms.